Transcranial Direct Current Stimulation of the Dorsolateral Prefrontal Cortex for Treatment of Neuropsychiatric Disorders - Li, Qing; Fu, Yu; Liu, Chang; Meng, Zhiqiang (Frontiers in Behavioral Neuroscience, 2022)
Background The dorsolateral prefrontal cortex (DLPFC) is a key node of the frontal cognitive circuit. It is involved in executive control and many cognitive processes. Abnormal activities of DLPFC are likely associated with many psychiatric diseases. Modulation of DLPFC may have potential beneficial effects in many neural and psychiatric diseases. One of the widely used non-invasive neuromodulation technique is called transcranial direct current stimulation (or tDCS), which is a portable and affordable brain stimulation approach that uses direct electrical currents to modulate brain functions. Objective This review aims to discuss the results from the past two decades which have shown that tDCS can relieve clinical symptoms in various neurological and psychiatric diseases. Methods Here, we performed searches on PubMed to collect clinical and preclinical studies that using tDCS as neuromodulation technique, DLPFC as the stimulation target in treating neuropsychiatric disorders. We summarized the stimulation sites, stimulation parameters, and the overall effects in these studies. Results Overall, tDCS stimulation of DLPFC could alleviate the clinical symptoms of schizophrenia, depression, drug addiction, attention deficit hyperactivity disorder and other mental disorders. Conclusion The stimulation parameters used in these studies were different from each other. The lasting effect of stimulation was also not consistent. Nevertheless, DLPFC is a promising target for non-invasive stimulation in many psychiatric disorders. TDCS is a safe and affordable neuromodulation approach that has potential clinical uses. Larger clinical studies will be needed to determine the optimal stimulation parameters in each condition.